Theoretical study of doped porous silicon in cantor quasi periodic structure for gamma radiation detection - Zaky A. Zaky; Taher S. Hassan; V. D. Zhaketov; Mohamed S. El Tokhy; Mohammed Sallah (Scientific Reports)
Abstract This study looks at two photonic crystals that are similar to Cantor’s and are separated by a thin layer of sensitive, porous silicon made of poly(ethylene oxide) nanocomposite and potassium iodide, which is used as a gamma indicator. Modifications in the distinct peak versus the irradiation dose track how the proposed indicator responds to radiation. The results demonstrate that gamma radiation alters the refractive index of the poly(ethylene oxide) nanocomposite, causing the distinct peaks to shift. The impact of doping of nanocomposite with potassium iodide, the porosity of silicon, and the cell’s number is analyzed. Doping the sensitive nanocomposite with potassium iodide showed a negative effect. The proposed indicator recorded a high sensitivity of 0.218 nm/Gy (nm/Gy = nanometer/gray) for low gamma doses up to 100 Gy, and a moderated sensitivity of 0.13 nm/Gy for high gamma dose from 100 to 200 Gy. The suggested indicator demonstrated high sensitivity in low gamma detection.